2015
DOI: 10.1371/journal.pone.0122752
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane Inhibits Nuclear Factor-κB Activation in Lipopolysaccharide-Induced Acute Inflammatory Lung Injury via Toll-Like Receptor 4 Signaling

Abstract: BackgroundInfection is a common cause of acute lung injury (ALI). This study was aimed to explore whether Toll-like receptors 4 (TLR4) of airway smooth muscle cells (ASMCs) play a role in lipopolysaccharide (LPS)-induced airway hyperresponsiveness and potential mechanisms.Methods In vivo: A sensitizing dose of LPS (50 µg) was administered i.p. to female mice before anesthesia with either 3% sevoflurane or phenobarbital i.p. After stabilization, the mice were challenged with 5 µg of intratracheal LPS to mimic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 37 publications
(55 reference statements)
1
23
0
1
Order By: Relevance
“…Three pathways involved in vitamin metabolism were also significantly altered, which was consistent with the fact that vitamin C supplementation offers significant protection against anesthetic-induced neurotoxicity and behavioral alterations, as proposed by Xu et al ( 27 ). Seven pathways involving the Toll like receptor (TLR) were significantly altered, which is consistent with the report by Sun et al which demonstrated that sevoflurane exerts direct relaxant and anti-inflammatory effects by inhibiting the TLR4/ nuclear factor-κB pathway ( 28 ). The present results indicate that these identified pathways were closely related to sevoflurane treatment, and suggest that special attention should be given to patients with correlated diseases when administering sevoflurane anesthesia.…”
Section: Discussionsupporting
confidence: 89%
“…Three pathways involved in vitamin metabolism were also significantly altered, which was consistent with the fact that vitamin C supplementation offers significant protection against anesthetic-induced neurotoxicity and behavioral alterations, as proposed by Xu et al ( 27 ). Seven pathways involving the Toll like receptor (TLR) were significantly altered, which is consistent with the report by Sun et al which demonstrated that sevoflurane exerts direct relaxant and anti-inflammatory effects by inhibiting the TLR4/ nuclear factor-κB pathway ( 28 ). The present results indicate that these identified pathways were closely related to sevoflurane treatment, and suggest that special attention should be given to patients with correlated diseases when administering sevoflurane anesthesia.…”
Section: Discussionsupporting
confidence: 89%
“…ALI, a kind of severe lung infectious disease, is mainly caused by bacterial infection-induced sepsis. LPS, the main component of the cell wall of gram negative bacteria, is the major pathogenic factor of ALI ( 9 ). LPS interacts with the receptor on the effector cell membrane to initiate an intracellular signal transduction system, which causes the activation of nuclear transcription factor NF-κB, to initiate gene transcription and to produce a variety of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear factor (NF)-κB collectively refers to many DNA binding proteins which specifically bind to κB site of promoters of a variety of genes, and promotes transcription, which plays an important role in immune response, inflammatory response and cell growth regulation ( 7 ). NF-κB signal pathway is the most important downstream pathway among all signal transduction pathways mediated by LPS, suggesting that TLR4/NF-κB pathway may be the key target to trigger inflammatory response and organ injury ( 9 ). Zhang and Xu ( 10 ) has indicated that miRNA-140-5p regulates hypoxia-mediated human pulmonary artery smooth muscle cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…ALI is characterized by an uncontrolled inflammatory response in the lungs, resulting in airway dysfunction (3). The most common cause of ALI is an exposure to the structural component of a Gramnegative bacterial membrane, lipopolysaccharide (LPS) (4). In response to bacterial LPS stimulation, neutrophils migrate across the endothelium and epithelium into the alveolar space, and are subsequently activated, causing the excessive production of proinflammatory molecules, such as reactive oxygen species (ROS) and pro-inflammatory cytokines (5).…”
Section: Introductionmentioning
confidence: 99%